Fauna carrion associated to domestic pig (Sus scrofa) in a coastal environment in Chubut, Argentina. (2017)
This is the first study of cadaveric decomposition taking place in a riverside environment of the NW of Chubut province, Argentina. The specific composition, abundance, diversity of the carrion fauna associated with a porcine experimental model was determined. Seasonal samplings were performed for three consecutive years (2010- 2012) using three domestic pigs for each sample, placed in wooden cages covered with wire mesh. Daily, insects were collected in the body, under and around it. There were identified and characterized the five stages of bodies’ decomposition of experimental pigs. Were collected 6,325 individuals adult and immature of 63 species belonging to 18 families distributed among the Diptera, Coleoptera and Hymenoptera orders. During the warm season, was determined the seasonality of Compsomyiops fulvicrura (Diptera: Calliphoridae) and, the dominance of Calliphora vicina (Diptera: Calliphoridae) in the cold season. Relevant information on the saprophagous insects in the riverside environment Chubut, which is helpful in estimating the time of death in forensic cases in the study region.